2019
DOI: 10.1021/acs.iecr.9b01188
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic Calcium Aluminate Cement with Super Mechanical Stability

Abstract: In the present study, a simple and cost-effective method for the preparation of a superhydrophobic calcium aluminate cement (SCAC) with superstable mechanical stability is reported. Room-temperature vulcanized silicone rubber (RTV) is used as an internal hydrophobic additive in concrete. The as-prepared cement surface and all cross-sections exhibit superhydrophobicity. The mechanical stability of the superhydrophobic-cement sample was evaluated by multiple severe mechanical damages. The SCAC sample exhibits su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…The corrosion inhibition efficiency (η) , can be calculated as follows where i corr and i corr 0 are the corrosion current density for the samples with and without superhydrophobicity, respectively. In general, a low i corr with a positive E corr as well as a high R p corresponds to the outstanding corrosion resistance. When compared to a bare aluminum alloy ( i corr = 29.33 μA·cm –2 ), the superhydrophobic samples showed low i corr , high R p , and a considerably positive shift in E corr . The results indicated that the superhydrophobic surface is able to improve the anticorrosion performance of metal.…”
Section: Resultsmentioning
confidence: 96%
“…The corrosion inhibition efficiency (η) , can be calculated as follows where i corr and i corr 0 are the corrosion current density for the samples with and without superhydrophobicity, respectively. In general, a low i corr with a positive E corr as well as a high R p corresponds to the outstanding corrosion resistance. When compared to a bare aluminum alloy ( i corr = 29.33 μA·cm –2 ), the superhydrophobic samples showed low i corr , high R p , and a considerably positive shift in E corr . The results indicated that the superhydrophobic surface is able to improve the anticorrosion performance of metal.…”
Section: Resultsmentioning
confidence: 96%
“…To date, a variety of applications of calcium aluminate-containing materials have been reported, including catalyst 16 , electrides and ionic conductor 17 , superhydrophobic cement 18 , biomaterial for dentistry and orthopedic fields 19 , bone cement 20 , hard tissue repair 21 , nanocatalyst for biodiesel production 22 , and adsorbent to remove aqueous Cr(VI) 23 . However, a review of the literature reveals that there are no records of monocalcium aluminate (CaAl 2 O 4 ) being used to remove MG dye from aqueous media.…”
Section: Introductionmentioning
confidence: 99%
“…At present, researchers mostly use binders to improve the mechanical stability of superhydrophobic surfaces. Lu et al used adhesives to attach perfluorosilane-coated titanium dioxide nanoparticles to various materials . Adhesives were used to bond coatings to various substrates to create a strong, self-cleaning surface.…”
Section: Introductionmentioning
confidence: 99%